Contextos emergentes no Colégio de Aplicação: tessituras das docências na perspectiva inclusiva - Wisch, Tásia Fernanda (2020)
The present research is affiliated to the Training, Knowledge, and Professional Development field of study of the Postgraduate Program in Education at the Federal University of Santa Maria/RS (UFSM). Through this study, we aim to understand how teachers learn to teach in the context of inclusive education. To this purpose, we posed the following question that will guide this research: how do the inclusive processes motivate the learning and teaching processes of teachers who work at the Colégio de Aplicação?. To answer this question, we listed the following main goal: to understand how the teachers of Colégio de Aplicação- CAp/UFRGS learn how to teach in the inclusive context. To carry out this study, we have chosen the sociocultural narrative approach as our methodology, which is based on qualitative research. The authors who support this approach are Bolzan (2001, 2007, 2017, 2019), Vygotski (2007, 2009, 2012), Bakhtin (2006), and Clandinin and Connelly (1995, 2015), Rossetto et al (2013). The research findings were produced and interpreted based on narrative interviews through which the teachers who collaborated in the study stated the ideas and paths that make up their teaching practices and how these elements influence the organization of their pedagogical work. The theoretical considerations that guided the understanding of teaching were based on Vygotski (2003a, 2003b, 2004, 2007, 2010, 2012a, 2012b) Leontiev (1978, 1984, 1988), Marcelo (1999), Vaillant and Marcelo (2012), Tardif (2014), Tardif and Lessard (2014a, 2014b), Imbernón (2009, 2010, 2015, 2016) and in the Brazilian context we relied on Freire (2013, 2016, 2018a, 2018b), Bolzan (2002, 2007, 2009), Arroyo (2013, 2014), Isaia (2010). Inclusive processes were discussed in the light of Freire (2013), Valle and Connor (2014), Carvalho (2010), Mantoan (2003, 2006, 2008), Diniz, (2007), Diniz et al (2009), Pletch (2014, 2020), Baptista (2009, 2011, 2013, 2019) and Freitas (2008). When addressing emerging contexts, we based ourselves on the studies of Morosini (2014, 2016) and Bolzan (2017, 2019). International documents and Brazilian legislation also contributed to support the debates. As a result, this research was shaped by the development of a category that is concerned with "being a teacher" and the "inclusive processes", which we called "Teacher learning". Such category is grounded on the notion that it is not possible to understand the teacher's profession without considering a continuous process of construction and [re]construction of pedagogical practices in the face of the realities experienced. And these realities are understood as emerging contexts, which run through teaching with the constant challenges and possibilities that arise in everyday school life. We concluded this research by pointing out that inclusive processes need to be seen as an organizing principle of the teaching practice, which requires a continuous learning process. Likewise, we highlight the importance of envisioning tangible actions in the scope of basic education, as a way to understand that the label of disability should not be the underlying premise when it comes to the inclusive perspective. On the contrary, difference and diversity are characteristics that are present in the human being, in the school, and in the relationships that are built there.